Poétique du roman algérien de langue française du XXIe: état des lieux et itinéraire - Chafik , Zeghnouf; Lilia , Boumendjel (Journal of Ecohumanism, 2025)
At the dawn of the 21st century, the Algerian novel in the French language is undergoing a profound transformation of its forms, its voices, and its concerns. As the period of "literature of urgency" draws to a close, a new generation of writers is decisively turning towards a quest for meaning, an inner exploration, and unprecedented formal experimentation. This evolution reflects a desire to reconcile memory and modernity, heritage and innovation, within a post-conflict context marked by the reconfiguration of identities and the broadening of cultural horizons. This study therefore aims to analyze the ways in which contemporary Francophone Algerian literature is reinventing its poetics, navigating between historical anchoring, cultural hybridity, and universal openness. To do this, it adopts the methodological framework of the historical poetics of literary communication, which allows us to apprehend the works as acts of communication embedded within a complex ecosystem integrating conditions of production, narrative innovations, and new modes of reception.